Ventral prefrontal cortex is not essential for working memory - Rushworth, M; Nixon, P; Eacott, M; Passingham, R (Society for Neuroscience, 1997)
It is widely held that the prefrontal cortex is important for working memory. It has been suggested that the inferior convexity (IC) may play a special role in working memory for form and color (Wilson et al., 1993). We have therefore assessed the ability of monkeys with IC lesions to perform visual pattern association tasks and color-matching tasks, both with and without delay. In experiment 1, six monkeys were trained on a visual association task with delays of up to 2 sec. Conservative IC lesions that removed lateral area 47/12 in three animals had no effect on the task. Further experiments showed that these lesions had no effect on the postoperative new learning of a color-matching task with delays of up to 2 sec or versions of the visual association task involving delays of up to 8 sec. In experiment 2, larger lesions of both areas 47/12 and 45A were made in the three control animals. This lesion caused a profound deficit in the ability to relearn simultaneous color matching, but subsequent matching with delays of up to 8 sec was clearly unimpaired. We suggest that the IC may be more important for stimulus selection and attention as opposed to working memory.